Tight coupling approach for networked control systems from cyber physical system perspective - Jin-zhi LIN; Ying WU; Gong-yi WU; Jing-dong XU (Tongxin xuebao)
From cyber physical system perspective,tightly coupling the communications and computing aspects with physical dynamics is profound.This characteristic is investigated for wireless networked control systems (WNCS).Following the tight coupling principle of CPS,a tight coupling adaptive fuzzy controlling methodology for WNCS is proposed.Through simulation experiments,it is showed that proposed method could adaptively adjust the controlled system's sample period and network channel access priority according to its real time control urgency and the network traffic condition,so as to optimize network utilization and improve the performances of the whole NCS.